Driving Halal Tourism in Lombok: The Role of Demographics, Islamic Lifestyles, and Vacation Preferences - Mukhlishin Mukhlishin; Ahadiah Agustina; Sahman Z.; Fathurrohman Husen; Mohamad Handi Khalifah (Shirkah: Journal of Economics and Business, 2025)
Despite the growing global demand for halal tourism, destinations such as Lombok (one of Indonesia’s prominent tourist regions) continue to face challenges in maximizing engagement within this niche market. This study addresses the critical gap by examining how demographic characteristics, Islamic lifestyles, and vacation preferences influence Muslim tourists’ interest in halal tourism in Lombok, West Nusa Tenggara. Using a quantitative survey design, data were collected from 235 Muslim tourists and analyzed through multiple regression using SPSS version 24. The findings indicate that all three variables significantly affect interest in halal tourism. Notably, vacation preferences emerged as the most influential factor, suggesting that Muslim tourists prioritize travel experiences that integrate leisure with faith-based values. Islamic lifestyle and demographics also demonstrated meaningful contributions, reinforcing the role of religious identity and sociodemographic traits in shaping travel behavior. These results underscore the need for tourism stakeholders to develop culturally aligned, spiritually fulfilling, and experience-driven tourism offerings. The study contributes theoretically to the growing body of literature on halal tourism behavior and offers practical insights for policymakers and destination managers seeking to enhance the appeal of Muslim-friendly tourism experiences.